Developing a Community-Based Participatory Research Model to Engage Transition Age Youth Using Mental Health Service in Research. Issue 1 (January 2015) - Lincoln, Alisa K.; Borg, Ryan; Delman, Jonathan
<x xml:space="preserve">Abstract</x> We present a model for the development and conduct of a community-based participatory research project with transition age youth (TAY) mental health service users. Community-based participatory research frameworks can facilitate equitable partnerships and meaningful inclusion but have not been fully drawn upon in mental health research. The model included TAY as trained research associates involved in every aspect of the research process. We describe the development of the project, creation of the research team, training, the design and conduct of the study, and challenges faced. The methods developed successfully provided support for the meaningful participation of TAY in the project.